Aktualisasi Kerukunan Masyarakat Beda Agama di Kelurahan Pager Kecamatan Rakumpit Kota Palangka Raya - Ajahari, Ajahari (Jurnal Studi Agama dan Masyarakat, 2018)
This study is aimed at finding out the ways of the different beliefs of peopleÂ  actualizing harmony, factors for people in actualizing the harmony and the role of religious leaders, traditional leaders and the local government in creating harmony in Pager Village. The research used the methods of observation, interviews and documentation. The results reveals that harmony in the Pager Village is well built, and it is original. 1) Actualization of inter-religious harmony is realized in the form of inviting and visiting each other during religious celebrations, activities of death, marriage and celebration. 2) The harmony, which is built is based on several factors such as theological factors, factors of philosophical values and local cultural wisdom such as belom bahadat values, hapaka basara, philosophy of Huma Betang teaching the values of harmony and togetherness; emotional factors and patriotic and nationalist values. 3) The creation of harmony and harmonious among residents in the Pager village is inseparable from the involvement of religious leaders, traditional leaders of each religion, the chief of the RT / RW who in their interaction and social behavior set a model to the people.